A mammalian inhibitory GDP/GTP exchange protein (GDP dissociation inhibitor) for smg p25A is active on the yeast SEC4 protein. - Sasaki, T (1991)
Evidence is accumulating that smg p25A, a small GTP-binding protein, may be involved in the regulated secretory processes of mammalian cells. The SEC4 protein is known to be required for constitutive secretion in yeast cells. We show here that the mammalian GDP dissociation inhibitor (GDI), which was identified by its action on smg p25A, is active on the yeast SEC4 protein in inhibiting the GDP/GTP exchange reaction and is capable of forming a complex with the GDP-bound form of the SEC4 protein but not with the GTP-bound form. These results together with our previous findings that smg p25A GDI is found in mammalian cells with both regulated and constitutive secretion types suggest that smg p25A GDI plays a role in both regulated and constitutive secretory processes, although smg p25A itself may be involved only in regulated secretory processes. These results also suggest that a GDI for the SEC4 protein is present in yeast cells.